A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages the arrangements to be made for the supply of drugs to patients attending Health Centres. As regards medical and surgical appliances, the existing system entitles an insured person to the supply, free of charge, of certain appliances specified in the Medical Benefit Regulations if ordered by a doctor. These "prescribed appliances" are, in the main, the articles most commonly required in general practice. In a service which includes treatment of all kinds, whether in or out of hospital, the range of necessary appliances will have to be greatly extended ; but it will be a matter for consideration whether the patient himself should not be called upon, if his financial resources permit, to contribute towards the cost of the more expensive appliances — or at least of repairs and replacements. This point will be of particular importance in connection with the dental and ophthalmic services. III. HOSPITALS Deficiencies in the present system A fully organised system of hospitals will be the keystone of the National Health Service. The new hospital service must be complete and ready of access. It must include general and special hospitals, infectious disease hospitals, sanatoria for tuberculosis, accommodation for maternity cases, for the chronic sick and for rehabilitation. Ancillary hospital services must also be provided — for pathological examination, X-ray, electro-therapy, ambulances, and other purposes. The high standard which many of the leading hospitals have attained needs no recommendation. They have shown the way in the development of hospital technique. But there are weaknesses in the present system and, to remedy these, two main problems have to be solved. The first is to enable the two main hospital systems to work closely together in future for a common purpose. The voluntary hospital movement is well known in this country, not only as the oldest established hospital system here, but also as a movement which attracts the interest and support of many people who believe in it as a social organisation and wish to see it maintained. Its co-operation is essential to the success of the new service, side by side with the other steadily developing system of the publicly provided hospitals of the local authorities. The Government's proposals are based on the fullest co-operation between the two hospital systems in one common service. The second problem is to determine the areas most suitable for hospital organisation, and bring together in a working plan for each area the various separate and independent hospitals. At present hospitals are not linked as they should be with one another and 36/H24/41